Анализа корелације нивоа цитокина у серуму и имунолошких фактора упале код циротичне портне хипертензије: Нивои цитокина у серуму и имуни инфламаторни фактори код циротичне порталне хипертензије - Yu, Yafeng; Lan, Zhiqiong; Huang, Zhi-Ren; Hu, Lingqin (Journal of Medical Biochemistry, 2025)
Objective: To investigate alterations in immune inflammatory factors and variables including procalcitonin (PCT), prostaglandin E (PGE), and serum C-reactive protein (CRP) in individuals with cirrhotic portal hypertension. Methods: From March 2020 to March 2025, 81 patients with cirrhotic portal hypertension and 50 healthy volunteers were hospitalized to our hospital. These people were divided into two groups: the portal hypertension group and the control group. Aspartate aminotransferase (AST), albumin (ALB), total bilirubin (TBIL), alanine aminotransferase (ALT), and portal vein inner diameter (Pvd) were measured. Serum cytokines such CRP, PCT, and PGE were measured, as well as CD4+/CD8+ T cell and CD3+, CD4+, and CD8+ T lymphocyte percentages. Results: The group with portal hypertension had considerably lower ALB than the control group (P<0.05), whereas indicators including ALT, AST, TBIL, and Dpv were significantly higher in the portal hypertension group than in the control group (P<0.05). While cytokine markers including CRP, PCT, and PGE were higher in the portal hypertension group than in the control group (P<0.05), the numbers of CD3+ and CD4+ T lymphocyte subsets and CD4+/CD8+ T lymphocytes were considerably lower in the portal hypertension group. With increasing liver function classification, the proportions of CD3+ and CD4+ T lymphocyte subsets and CD4+/CD8+ T lymphocytes in patients decreased. However, there was a statistically significant (P<0.05) increase in the levels of serum PCT, PGE, and CRP. Spearman correlation analysis revealed that liver function classification was negatively correlated with immune indicators CRP, PCT, and PGE levels were favorably connected with CD4+ and CD4+/CD8+ (P<0.05) values. Dpv was shown to have a negative association with CD4+/CD8+ T cells and a positive correlation with PCT and PGE levels (P<0.05) according to Pearson correlation analysis. Conclusion: Patients with cirrhotic portal hypertension may experience immune dysfunction and cytokine disorders. These changes are related to liver function and portal vein pressure and can be used as reference indicators for evaluating a patient’s condition in clinical practice.